Between Ostrogothic and Carolingian Italy Survivals, revivals, ruptures - Oppedisano, Fabrizio (Reti Medievali E-Book, 2022)
The victory of Justinian, achieved after a lacerating war, put an end to the ambitious project conceived and implemented by Theoderic after his arrival in Italy: that of a new society in which peoples divided by centuries-old cultural barriers would live together in peace and justice, without renouncing their own traditions but respecting shared principles inspired by the values of civilitas. What did this great experiment leave to Europe and Italy in the centuries to come? What were the survivals and the ruptures, what were the revivals of that world in early medieval society? How did that past continue to be recounted and how did it interact with the present, especially in the decisive moment of the Frankish conquest of Italy? This book aims to confront these questions, and it does so by exploring different themes, concerning politics and ideology, culture and literary tradition, law, epigraphy and archaeology.